Growth and oscillation of some polynomials generated by solutions of complex differential equations - Belaïdi, Benharrat; Latreuch, Zinelâabidine (Opuscula Mathematica, 2015)
In this paper, we continue the study of some properties on the growth and oscillation of solutions of linear differential equations with entire coefficients of the type f 00 + A(z)f 0 + B(z)f = 0 and f (k) + Ak−2(z)f (k−2) + . . . + A0(z)f = 0.
Keywords: Linear differential equations; finite order; exponent of convergence of the sequence of distinct zeros; hyper-exponent of convergence of the sequence of distinct zeros.